Challenges in Securing Data and Networks from Modern Cyber Threats - ⁠⁠⁠Irma Shantilawati; Jihan Zanubiya; Fajriannoor Fanani; Henrik Jensen; Shofiyul Millah; Ninda Lutfiani (International Journal of Cyber ​​and IT Service Management (IJCITSM), 2024)
In the era of digital transformation, organizations face an increasing array of cyber threats that target data and network security. This study focuses on the key challenges encountered in protecting sensitive information and network infrastructures from evolving cyberattacks, such as ransomware, phishing, and advanced persistent threats. The objective is to explore the current landscape of cyber threats and identify the major hurdles in implementing effective security measures. Through a mixed-method approach involving surveys and case studies, the research highlights the skills gap, complexity of network architectures, and the rapid advancement of threats as primary obstacles. The findings underscore the need for advanced security solutions, such as AI-driven threat detection and zero trust models, to enhance organizational resilience. Addressing these challenges is critical to safeguarding data, ensuring business continuity, and maintaining regulatory compliance.